A tumor‐targeting nanomedicine carrying the p53 gene crosses the blood–brain barrier and enhances anti‐PD‐1 immunotherapy in mouse models of glioblastoma. Issue 9 (8th July 2019) - Kim, Sang‐Soo; Harford, Joe B.; Moghe, Manish; Slaughter, Tiffani; Doherty, Caroline; Chang, Esther H.
Abstract : Despite its anticipated clinical potential, anti‐PD‐1 immunotherapy has only yielded poor outcomes in recent clinical trials for glioblastoma patients. Strategies combining anti‐PD‐1 antibody with other treatment modalities are being explored to alter the immunosuppressive microenvironment that appears to characterize these anti‐PD‐1‐insensitive tumors. Here, we evaluated whether introducing wild‐type p53 gene via a tumor‐targeting nanomedicine (termed SGT‐53) could provide immune stimulation and augment anti‐PD‐1 therapy in mouse syngeneic GL261 tumor models (either subcutaneous or intracranial). In both models, anti‐PD‐1 monotherapy had no demonstrable therapeutic effect. However, combining anti‐PD‐1 with our investigational nanomedicine SGT‐53 was very effective in inhibiting tumor growth, inducing tumor cell apoptosis and increasing intratumoral T‐cell infiltration. A significant survival benefit was observed in mice bearing intracranial glioblastoma receiving combination treatment. Importantly, SGT‐53 upregulated PD‐L1 expression both in vitro and in vivo . Transcriptome analysis revealed modulation of genes linked to either cancer progression or immune activation after combination treatment. Our data suggest that SGT‐53 can boost antitumor immunity and sensitize glioblastoma to anti‐PD‐1 therapy by converting immunologically "cold" tumors into "hot" tumors. Combining SGT‐53 with anti‐PD‐1 might benefit more patients from anti‐PD‐1 immunotherapy and our data support evaluation of this combination in patients with glioblastoma. Abstract : What's new? Antibodies targeting the programmed cell death protein 1 (anti‐PD‐1) pathway represent a promising immunotherapeutic strategy against glioblastoma. Nonetheless, in recent trials, significant numbers of glioblastoma patients failed to respond to anti‐PD‐1. Here, the authors explored the possibility of overcoming this insensitivity by combining anti‐PD‐1 with SGT‐53, a tumor‐targeting nanomedicine that restores p53 function. In glioblastoma mouse models, the combined immunotherapy approach effectively inhibited tumor growth and increased intratumoral infiltration of immune effector cells. Increased immunogenicity was associated with significant survival benefits. The data provide a strong mechanistic rationale for combining SGT‐53 nanomedicine and anti‐PD‐1 immunotherapy in the treatment of glioblastoma.